2012
DOI: 10.1104/pp.112.199208
|View full text |Cite
|
Sign up to set email alerts
|

Complexes with Mixed Primary and Secondary Cellulose Synthases Are Functional in Arabidopsis Plants    

Abstract: In higher plants, cellulose is synthesized by so-called rosette protein complexes with cellulose synthases (CESAs) as catalytic subunits of the complex. The CESAs are divided into two distinct families, three of which are thought to be specialized for the primary cell wall and three for the secondary cell wall. In this article, the potential of primary and secondary CESAs forming a functional rosette complex has been investigated. The membrane-based yeast two-hybrid and biomolecular fluorescence systems were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 63 publications
7
74
0
1
Order By: Relevance
“…Interestingly, there were also PCW CesAs that showed similar expression patterns as pectin and xyloglucan biosynthesis genes, with high transcript abundances during SCW biosynthesis, bringing into question their PCW specificity. A functional role for PCW CesAs during SCW biosynthesis is supported by the presence of protein complexes containing both PCW and SCW CesAs in xylem cells synthesizing SCW layers (Song et al, 2010;Carroll et al, 2012). Thus, what are referred to as PCW CesA genes might have a more general role than previously thought, including the possibility that they enter into complexes with SCW CesAs.…”
Section: Primary Cell Wall Polysaccharide Biosynthetic Genes Continuementioning
confidence: 72%
“…Interestingly, there were also PCW CesAs that showed similar expression patterns as pectin and xyloglucan biosynthesis genes, with high transcript abundances during SCW biosynthesis, bringing into question their PCW specificity. A functional role for PCW CesAs during SCW biosynthesis is supported by the presence of protein complexes containing both PCW and SCW CesAs in xylem cells synthesizing SCW layers (Song et al, 2010;Carroll et al, 2012). Thus, what are referred to as PCW CesA genes might have a more general role than previously thought, including the possibility that they enter into complexes with SCW CesAs.…”
Section: Primary Cell Wall Polysaccharide Biosynthetic Genes Continuementioning
confidence: 72%
“…Furthermore, ectopic overexpression of fra5, a dominant mutant of CESA7 affects cell wall formation in both types of walls (Zhong et al, 2003). In a genetic swap experiment, CESA7, under the expression of the CESA3 promoter, can partially complement the growth defect of cesa3 je5 , indicating that CESA7 may have structural properties allowing its incorporation into primary CSCs (Carroll et al, 2012). On the other hand, CESA1, under a promoter of a secondary CESA gene, partially complemented cesa8 irx1 null mutant phenotypes, including defects in cellulose content, plant stature and collapsed xylem vessels (Carroll et al, 2012;.…”
Section: Colmentioning
confidence: 99%
“…In a genetic swap experiment, CESA7, under the expression of the CESA3 promoter, can partially complement the growth defect of cesa3 je5 , indicating that CESA7 may have structural properties allowing its incorporation into primary CSCs (Carroll et al, 2012). On the other hand, CESA1, under a promoter of a secondary CESA gene, partially complemented cesa8 irx1 null mutant phenotypes, including defects in cellulose content, plant stature and collapsed xylem vessels (Carroll et al, 2012;. Interestingly, a phylogenetic analysis revealed that the separation of primary and secondary CESAs may have occurred before the appearance of vascular plants (Carroll et al, 2011).…”
Section: Colmentioning
confidence: 99%
“…Carroll et al reported that all primary CESAs (CESA1, CESA3 and CESA6) interacted with secondary CESAs (CESA4, CESA7 and CESA8) in a split-ubiquitin Y2H assay. 12 We cannot examined in all transgenic lines. P7C1 partially complemented several irx1 cesa8 growth defects such as dwarf stature, reduced fertility, reduced leaf size and short siliques (Fig.…”
Section: Functional Analysis Of Complexes With Mixed Primary and Secomentioning
confidence: 99%